Nepal : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Nepal showed satisfactory macroeconomic performance despite difficult political circumstances. Executive Directors welcomed the comprehensive program of structural reforms that aimed at poverty reduction, and stressed the need for prudent macroeconomic policies. They appreciated the authorities' strategy to address the negative net worth of the two largest banks, and strengthen the financial sector. They encouraged the authorities to maintain an open trade and investment regime, encourage access to world banks, implement the recommendations of the IMF's multisector statistics mission, and improve the macroeconomic database.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet